(untitled) (Higher Education Politics and Economics, 2019)
The purpose of this study was to determine the extent to which the Trump administration ban on individuals from 7 Muslim-majority countries (i.e., Executive Order 13769), influenced prospective international graduate applicants to two Texas institutions. Inferential statistical procedures revealed the presence of a statistically significant, sharp decline in international graduate applicants, particularly from Muslim-majority countries. From Fall 2016 to Fall 2018, international graduate applicants from non-Muslim-majority countries declined 18.36%. Over this same time period, applicants from Muslim-majority countries declined 33.37%. Most notably, applicants from the 7 countries targeted in the travel ban declined 53.93%. Concerns clearly exist regarding the effects of this travel ban on international student mobility. Implications of these findings and recommendations for future research are discussed.